2011
DOI: 10.1039/c0cp02654a
|View full text |Cite
|
Sign up to set email alerts
|

Dual fluorescence in 9-amino-2,7,12,17-tetraphenylporphycene

Abstract: The absorption spectrum of the asymmetric 9-amino-2,7,12,17-tetraphenylporphycene shows new, strongly red-shifted bands compared to the symmetric parental 2,7,12,17-tetraphenylporphycene and to the also asymmetric 9-acetoxy-2,7,12,17-tetraphenylporphycene. Dual emission is also observed with relative contributions that depend strongly on the excitation wavelength and temperature. The gap between the two fluorescence bands is 84 nm. Tautomerization in both the ground and excited states is shown to account for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 22 publications
2
38
0
Order By: Relevance
“…The same conclusion has been drawn previously, basing on different F 1 and F 2 fluorescence-decay times and on different excitation spectra in toluene and 2methyltetrahydrofuran. [32] Interestingly, whereas the excitation-and absorption spectra are very different for F 2 , they strongly resemble each other for F 1 .…”
Section: Wwwchemeurjorgmentioning
confidence: 91%
See 1 more Smart Citation
“…The same conclusion has been drawn previously, basing on different F 1 and F 2 fluorescence-decay times and on different excitation spectra in toluene and 2methyltetrahydrofuran. [32] Interestingly, whereas the excitation-and absorption spectra are very different for F 2 , they strongly resemble each other for F 1 .…”
Section: Wwwchemeurjorgmentioning
confidence: 91%
“…We compare 2,7,12,17-tetraphenylporphycene (TPPo) with 9-amino-2,7,12,17-tetraphenylporphycene (9-ATPPo, Scheme 1). Previous studies of 9-ATPPo [32,33] revealed quite unique properties of this molecule. Dual fluorescence was observed and the energy gap between the two bands exceeded 1500 cm À1 .…”
Section: Introductionmentioning
confidence: 90%
“…Of particular interest is the N-H tautomerization process in 9-substituted asymmetric porphycene derivatives as high electron-donating substituents in the 9-position leads to an enhanced energetic-splitting between the two transtautomers resulting in dual fluorescence emission. [17][18][19] In contrast,…”
Section: Introductionmentioning
confidence: 97%
“…No spectral changes could be observed in either case, which rules out protonation of the pyrrole nitrogens as the underlying cause for the observed results for ATAZPo 2 and sets this molecule apart of any porphycene reported so far. Prompted by our previous observations that the tautomers of asymmetric 9-amino porphycenes showed distinct red and near-IR absorption and fluorescence spectra, 17,18 we next considered the possibility that the two extreme spectra observed for the also asymmetric ATAZPo 2 could correspond to two tautomers as well, whose relative population would be affected by the solvent properties. The absorption spectra of 9-amino-2,7,12,17-tetrakis(2-methoxy ethyl) porphycene in HFIP and in THF (Fig.…”
Section: Solvent and Acid Effects On Other Porphycenesmentioning
confidence: 99%
See 1 more Smart Citation